2020
DOI: 10.21474/ijar01/11582
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Potassium and Humic Acid on Productivity and Fruit Quality of Wonderful Pomegranate Variety

Abstract: A two-year trial was conducted during 2017 and 2018 seasons on Wonderful pomegranate orchard about 7 years old grown in sandy soil under drip irrigation system from well at private orchard located on Cairo-Alexandria desert road (about 50km from Cairo), Egypt. Potassium fertilizer at 250 and 350g /tree/ year alone and/or humic acid at 20 and 30g/ tree/year, added as a soil application divided into two equal doses applied at two times a year in the first week of May and July in both seasons. Generally, all test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
2
0
0
Order By: Relevance
“…The improved effect of humic acids on fruit quality may be attributed to that humic acid stimulates plant growth and consequently fruit quality through accelerating cell division and it enhances the uptake of nutrients and water (Chen et al, 2004;Abdel Fatah et al, 2008 andHussein andHassan, 2011) and humic acid has similar effect like IAA on plants in this concern (Nardi et al, 2002), subsequently, it improves fruit quality. The obtained results of humic acid on improving fruit quality are in agreement with the findings of Abbas et al (2013) on mandarin;Olyaie Torshiz et al (2017) and Salama et al (2020) on pomegranate. The obtained results of the interaction between manure and humic acid on fruit quality go in line with the findings of Mansour (2018) on pomegranate.…”
Section: Fruit Ascorbic Acid Contentsupporting
confidence: 91%
See 1 more Smart Citation
“…The improved effect of humic acids on fruit quality may be attributed to that humic acid stimulates plant growth and consequently fruit quality through accelerating cell division and it enhances the uptake of nutrients and water (Chen et al, 2004;Abdel Fatah et al, 2008 andHussein andHassan, 2011) and humic acid has similar effect like IAA on plants in this concern (Nardi et al, 2002), subsequently, it improves fruit quality. The obtained results of humic acid on improving fruit quality are in agreement with the findings of Abbas et al (2013) on mandarin;Olyaie Torshiz et al (2017) and Salama et al (2020) on pomegranate. The obtained results of the interaction between manure and humic acid on fruit quality go in line with the findings of Mansour (2018) on pomegranate.…”
Section: Fruit Ascorbic Acid Contentsupporting
confidence: 91%
“…Moreover, humic acid has similar effect like IAA in plants (Nardi et al, 2002). The obtained results of humic acid application on cladodes nutrients content are in harmony with the findings of Salama et al (2020) on pomegranate trees and Razavi-Nasab et al ( 2019) on pistachio. Besides, Danyaei et al (2017) found that humic acid application enhanced leaf N, P, K, Fe, Mn, Zn and Cu content of olive.…”
Section: Cladodes Micro-nutrients Contentsupporting
confidence: 85%